Detecting Noise-Induced Cochlear Synaptopathy by Auditory Brainstem Response in Tinnitus Patients With Normal Hearing Thresholds: A Meta-Analysis - Chen, Feifan; Zhao, Fei; Mahafza, Nadeem; Lu, Wei (Frontiers in Neuroscience, 2021)
Noise-induced cochlear synaptopathy (CS) is defined as a permanent loss of synapses in the auditory nerve pathway following noise exposure. Several studies using auditory brainstem responses (ABR) have indicated the presence of CS and increased central gain in tinnitus patients with normal hearing thresholds (TNHT) but the results were inconsistent. This meta-analysis aimed to review the evidence of CS and its pathological changes in the central auditory system in TNHT. Published studies using ABR to study TNHT were reviewed. PubMed, EMBASE and Scopus databases were selected to search for relevant literature. 489 studies were retrieved and 11 were included for meta-analysis. The results supported significantly reduced wave I amplitude in TNHT, whereas the alternations of wave V amplitude were inconsistent among the studies. Consistently increased V/I ratio indicated noise-induced central gain enhancement. The results indicated the evidence of noise-induced cochlear synaptopathy in tinnitus patients with normal hearing. However, inconsistent changes of wave V amplitude may be explained by that the failure of central gain that triggers the pathological neural changes in the central auditory system and/or that increased central gain may be necessary to generate tinnitus but not to maintain tinnitus.